Rapid Characterization and Identification of Chemical Constituents in Gentiana radix before and after Wine-Processed by UHPLC-LTQ-Orbitrap MSn - Xin Lv; Jian-Zhi Sun; Shi-Zhao Xu; Qian Cai; Yu-Qiang Liu (Molecules, 2018)
Gentiana radix is used in traditional Chinese medicine and has functions of clearing heat and drying dampness, as well as purging liver and gallbladder fire. A highly sensitive and effective strategy for rapid screening and identification of target constituents has been developed by using ultra high-performance liquid chromatography coupled with linear ion trap-Orbitrap mass spectrometry (UHPLC-LTQ-Orbitrap) in crude and wine-processed Gentiana radix. Based on the accurate mass measurement (<5 ppm), retention times, and MS fragmentation ions, 52 constituents were unambiguously or tentatively characterized from Gentiana radix, including 21 iridoids, 11 flavonoids, 19 xanthones, and a triterpenoid. This study demonstrated that the established method could be a rapid, effective analytical tool for screening and characterization of compounds in the complex systems of Gentiana radix. By comparing the structure and peak areas of chemical constituents in crude and wine-processed Gentiana radix, we found that some compounds in crude and wine-processed Gentiana radix were significantly different.